Building government portals that work: guiding principles from Community Informatics. (2nd January 2008) - Ruhi, Umar; Takala, Paul; Detlor, Brian; Hupfer, Maureen
As governments implement new digital environments as a means of delivering better information services and resources, building rich digital spaces that encourage citizen uptake is becoming an increasing challenge. This paper addresses this issue and examines the City of Hamilton's municipal portal, called myhamilton. To understand what governments need to do to secure successful implementation of comprehensive digital spaces that are relevant to citizens, myhamilton is used to showcase practical guidelines from key managers involved in the portal project. These guidelines are discussed within the backdrop of best practices from the Community Informatics (CI) literature.